Implementation of Public Sector Audit Committee Guidelines: A Case Study of the Ministry of Finance Audit Committee - Novia Ramadhan; Lindawati Gani (Jurnal Ilmiah Akuntansi, 2023)
This study critically examines the implementation of public sector audit committee guidelines within the MoF Audit Committee. Employing a comprehensive case study approach, the research delves into primary documents and conducts structured and semi-structured interviews with both the MoF Audit Committee and relevant stakeholders. Guided by best practices outlined in H.M. Treasury’s Audit and Risk Assurance Committee Handbook and the IIA’s Independent Audit Committees in Public Sector Organizations, the study establishes that the MoF has successfully instituted an audit committee in adherence to the principles and elements prescribed for public sector audit committees. While acknowledging this achievement, the research also identifies areas warranting improvement in the implementation of the audit committee. These findings underscore the importance of continual refinement to ensure optimal effectiveness and alignment with evolving best practices. The study contributes valuable insights to the discourse on public sector audit committee performance, offering practical recommendations for the MoF and other entities seeking to enhance their audit committee implementations within the broader context of public sector governance.